Robots in the smart home: a project towards interoperability. (19th May 2011) - De La Pinta, J.R.; Maestre, J.M.; Camacho, E.F.; Alonso, I. Gonzalez
In this paper, it is addressed the problem of integrating service robots in the smart home. To this end, several middleware initiatives are analysed, paying special attention to Universal Plug and Play (UPnP). In addition, the iRobot service robot Roomba is deeply studied and an application to integrate it in the smart home via UPnP is presented.